Penyusunan Bibliografi Beranotasi Buku Subjek Penyakit dalam Koleksi Perpustakaan Fakultas Kedokteran Universitas Andalas - Nova, Olga Ulya; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Â Abstract Â The writing of this paper aims to: (1), describe an annotated bibliography of internal medicine subject books for a collection of textbooks at the Andalas University Medical School Library. (2), explain the constraints and efforts faced in preparing an annotated bibliography of internal medicine subjects in the Library of the Faculty of Medicine, Andalas University. The research method used is descriptive method, which is collecting data directly from the source. Data was collected through direct observation at the Andalas University Medical School, the number of books contained in the library subjected to internal diseases as many as 52 book titles. classifying the collection of internal medicine subjects, typing book annotations, typing the name of the author, year of publication, title of the book, and typing the index of keywords and finally compiled sequentially according to the modern language association (MLA) format which can describe quotes more fully and accurately with all sources research printed for example books. The results obtained in the bibliographic preparation stage are First, the determination of the title of the book is done by the availability of clothing collections by visitors. Second, Collection of library materials by searching directly and collecting books one by one. Third, the selection of library materials is done by separating the internal subject books with the surgical subject book. Fourth, grouping library material is done so that it collects with the same subject book by using sequence number numeral notation. Fifth, Making keywords is done by taking words from the title or content in a striking book. Sixth, Index Compilation aims to facilitate the search for information needed. Seventh, Typing a bibliographic text is done in the format of the Modern Language Association (MLA). Eighth, Examination of the final bibliographic text aims to see whether the writing is correct or not.Keywords: bibliography, annotations, internal diseases